Pentingnya Perawatan Mooring Line di MV. Bali Kuta untuk Kelancaran Berthing - Mudiyanto; Pamungkas, Putra Anugrah (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2019)
This study aims to explain the importance of Mooring Line maintenance in MV. Bali Kuta for smooth berthing. The background is the lack of maintenance of the Mooring Line and the Ship Harbor Kit, which has an impact on the smooth berthing. Lack of maintenance on Mooring Line can cause delay on the ship and damage to the Mooring Line which can be fatal. The purpose of this study is to understand and apply proper and proper care for Mooring Lines on MV. Bali Kuta. The approach used in this research is descriptive approach. If the data has been collected then classified into two groups of data, namely quantitative in the form of numbers and qualitative data expressed in words or symbols. Qualitative data in the form of words is temporarily set aside, because it will be very useful to accompany and complete the picture obtained from quantitative data analysis. The results of this study are to avoid mall functions or errors in the harbor and ship harness kit, so various methods and actions are required for maintenance on the ship harbor kit equipment in accordance with applicable regulations. In the implementation of rope care requires knowledge of the rope, based on education and experience in handling the rope, and carried out with discipline in its implementation. Discipline is a determining factor in the success of a maintenance job.